Pengaruh Kualitas Produk, Persepsi Harga, dan Citra Merek terhadap Keputusan Pembelian (Studi di Antariksa Kopi Semarang) - Bagus Kapirossi; Rokh Eddy Prabowo (Ekonomis: Journal of Economics and Business, 2023)
Coffe Shop or a coffee shop is a place whose main focus is selling various types of coffee-based drinks. In Semarang there are many coffee shops, one of the many that needs to be researched is Antariksa Kopi. The purpose of this study was to analyze the effect of each independent variable, namely product quality, price perception, and brand image on purchasing decisions at Semarang Kopi Semarang. The method used is quantitative method. The number of samples in this study were 97 respondents who were determined by the technique purposive sampling. The data analyzed were primary data collected using a questionnaire and processed using the SPSS version 26 program. Based on data processing, the following results were obtained, the instrument test stated that all indicators were valid and all variables were declared reliable. The test results of the coefficient of determination (R2) shows, the ability of the independent variable to explain the dependent variable is 65.5 percent. The results of the F test of all independent variables simultaneously influence purchasing decisions. The results of the regression coefficient and t test show that the variables of product quality, price perception, and brand image have a positive and significant effect on purchasing decisions at Antariksa Kopi Semarang.